(untitled) (Research, Society and Development, 2022)
Objective: production of a low-cost anatomical piece of the eye for the visually impaired. Methodology: This is an experimental, qualitative and descriptive study that aims to make an anatomical model of the old teaching-learning school, being made with low-custody materials as a stage for people with visual impairments. Results and discussion: A small anatomical surface appears on the surfaces of each small structure, relays and specific texture, where different structural molds were used for a differentiated tactile sensitivity of two visual impairments. Low-custody materials were chosen due to their greater durability, strength, manual malleability and heat, drying time, transparency and lightness, in addition to the use of a contrasting coloration on the anatomical body, allowing the visual stimulation of the low-level student. eyesight. Final Considerations: Given or exposed, it is concluded that the three-dimensional model, being made with low-guard materials, presents an alternative method of learning with students with visual impairment and low vision.